1990
DOI: 10.1159/000129075
|View full text |Cite
|
Sign up to set email alerts
|

Canine Pancreatic Islet Transplantation: A Comparison of Two Isolation Techniques

Abstract: A new method (type B) for isolation of canine islets was developed, utilizing intraductal collagenase perfusion, stationary digestion, filtration and tissue separation by means of a dextran density gradient. The results of this technique were compared with those of a previously established method (type A). Islets were autotransplanted either via the splenic or the portal vein. Lasting normoglycemia was obtained in 5/8 intrasplenic type B transplants (63%), 6/8 intrahepatic type B transplants (75%), 5/6 intrasp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Historically, intrasplenic islet transplantation has been performed since the late 1970s, when several trials of intrasplenic islet autotransplantation into pancreatectomized dogs demonstrated recovery of endocrine function [ 89 , 90 , 91 , 92 ]. This model has been used to assess transplantation efficacy [ 89 , 90 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ], and also to assess the transplantation of cold-preserved or cryopreserved islets [ 103 , 104 , 105 , 106 ] and the toxicity of immunosuppressants [ 95 , 107 , 108 , 109 , 110 ]. Other animals, including pigs [ 111 ] and monkeys [ 112 , 113 , 114 ], have also been used for islet autotransplantation and have shown acceptable outcomes.…”
Section: Outcomes Of Intrasplenic Islet Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, intrasplenic islet transplantation has been performed since the late 1970s, when several trials of intrasplenic islet autotransplantation into pancreatectomized dogs demonstrated recovery of endocrine function [ 89 , 90 , 91 , 92 ]. This model has been used to assess transplantation efficacy [ 89 , 90 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ], and also to assess the transplantation of cold-preserved or cryopreserved islets [ 103 , 104 , 105 , 106 ] and the toxicity of immunosuppressants [ 95 , 107 , 108 , 109 , 110 ]. Other animals, including pigs [ 111 ] and monkeys [ 112 , 113 , 114 ], have also been used for islet autotransplantation and have shown acceptable outcomes.…”
Section: Outcomes Of Intrasplenic Islet Transplantationmentioning
confidence: 99%
“…Using fetal porcine allotransplantation and murine transplantation models, Stokes et al showed a higher transplantation efficacy for the spleen compared with the liver, although the kidney was better [ 129 , 130 ]. Many other studies have reported superiority of the spleen compared with the liver [ 100 , 111 ] or omental pouch [ 56 , 131 ], although some groups have reported opposite results [ 97 , 98 , 99 ] ( Table 3 ).…”
Section: Outcomes Of Intrasplenic Islet Transplantationmentioning
confidence: 99%
“…Historically, intrasplenic islet transplantation has been performed since the late 1970s, when a number of trials looking at intrasplenic islet autotransplantation into pancreatomized dogs demonstrated that this method could result in the recovery of endocrinal function [87][88][89][90]. This model has been used not only for the assessment of transplantation efficacy [87,88,[90][91][92][93][94][95][96][97][98][99][100], but also for the assessment of the transplantation of cold or cryopreserved islets [101][102][103][104] and the toxicity of immunosuppressants [93,[105][106][107][108]. Other animals such as pig [109] and monkey [110][111][112] have also been used for islet autotransplantation and have shown acceptable outcomes.…”
Section: Characteristics Of the Spleen As An Islet Transplant Sitementioning
confidence: 99%
“…Using fetal porcine allotransplantation and murine transplantation models, Stokes et al showed higher transplantation efficacy for spleen compared to liver, although kidney was better [127,128]. Many other studies have reported the superiority of spleen compared to liver [98,109] or omental pouch [54,129], although some groups have reported the opposite [95][96][97] (Table 3).…”
Section: Characteristics Of the Spleen As An Islet Transplant Sitementioning
confidence: 99%